Hepatitis B e antigen and e antibody in a multi‐ethnic cohort of adult chronic hepatitis B virus patients followed at a single liver unit for a period of 20 years. Issue 10 (13th July 2022) - Mutimer, David; Elsharkawy, Ahmed; Hathorn, Emma; Arunkumar, Selvi
Abstract: Hepatitis B virus e antigen (HBeAg) loss and the appearance of antibodies to HBeAg (anti‐HBe) are favourable events in the history of chronic hepatitis B virus (CHB) infection. Most CHB patients have the HBeAg/anti‐HBe profiles +/− or −/+, and little is published on the derivation or fate of the +/+ and −/− profiles. We have used electronically accessible patient data to study the HBeAg and anti‐HBe profiles of a multi‐ethnic cohort of adult HBV patients seen at a single centre over a period of more than 20 years. 3594 HBsAg‐positive patients were identified and patients with viral coinfection or acute HBV infection were excluded. Cross‐sectional and longitudinal analyses of HBeAg/anti‐HBe status were undertaken. Compared with White or Black patients, Chinese and Asian patients are more likely to be HBeAg positive during child‐bearing years. Patients with +/+ profile are likely to undergo HBeAg loss and seroconversion during relatively short follow‐up. Chinese patients have a relatively increased rate of seroconversion. For HBeAg‐positive patients, the risk of seroconversion diminishes with advancing age. Despite HBeAg loss, seroconversion is seldom observed after age 60 years. The proportion of HBV patients with −/− increases with age, and most acquire this profile by HBeAg loss but without antecedent seroconversion. −/− patients can lose HBsAg and develop anti‐HBs. It was not possible to demonstrate a favourable impact of antiviral treatment on the rate of HBeAg seroconversion.